ANALISIS PENGENDALIAN KUALITAS PRODUK ROTI DENGAN MENGGUNAKAN PETA P DAN 7 TOOLS OF QUALITY - Gunawan Mohammad (Universitas Islam Nahdlatul Ulama Jepara, 2020)
PT Candrabuaya Surya Semesta is a company that produces catering and bread, one of which is located in the Jepara City. Increasing competition in the catering and bread business requires companies to be able to maintain and improve their quality to retain customers. The purpose of this study is to determine the level of product quality and to determine the factors that caused the quality of a product from the company. The sweet wet bread product is a superior product that more customer interested, so in this study (research) used analysis of product quality control with P maps and seven tools of quality. There are two main defects in the production process of sweet wet bread, namely the dough does not expand and baking is not perfect. Of the two defects, the defect of the dough does not develop into a priority proposal for improvements that must be done by the company. The common factors that cause disability are method factors in the production process, equipment used, human reliability factors, and materials / raw materials used.